Complete genome sequences of classical swine fever virus: Phylogenetic and evolutionary analyses - Liu, Yue; Bahoussi, Amina Nawal; Wang, Pei-Hua; Wu, Changxin; Xing, Li (Frontiers in Microbiology, 2022)
The classical swine fever virus (CSFV) outbreaks cause colossal losses of pigs and drastic economic impacts. The current phylogenetic CSFV groups were determined mainly based on the partial genome. Herein, 203 complete genomic sequences of CSFVs collected worldwide between 1998 and 2018 available on the GenBank database were retrieved for re-genotyping and recombination analysis. The maximum likelihood phylogenetic tree determined two main groups, GI and GII, with multiple sub-genotypes. The “strain 39” (GenBank ID: AF407339), previously identified as belonging to sub-genotypes 1.1 or 2.2 based on the partial sequences, is found to be genetically distinct and independent, forming a new lineage depicted as GI-2.2b. Ten potential natural recombination events were identified, seven of which were collected in China and found involved in the genetic diversity of CSFVs. Importantly, the vaccine strains and highly virulent strains were all involved in the recombination events, which would induce extra challenges to vaccine development. These findings alarm that attenuated vaccines should be applied with discretion and recommend using subunit vaccines in parallel with other preventive strategies for better management of CSFVs.